(untitled) (Global Journal of Human-Social Science, 2020)
Basically the followers of Kortavaza religion, the Bhogobania community originated in the middle of the 18th century. This community is guided by core six principles and if the people follow these principles, need not visit the doctor. In any cases, if they go to doctor then the preceptor of this community imposes some fines. For this reason they have a lot of medicinal plant knowledge among them which they use these herbs for head to toe treatment. Basically following the participant observation method this article has been prepared. The study focuses a single community covered forty households highlighting their demographic profile, socio economic condition and medicinal plant knowledge. This article points out thirty eight types of diseases, symptoms and remedies suggested by various types of herbs. The World Health Organization (WHO) has declared that it is possible to turn traditional healing practices into modern scientific medicine. And to materialize this possibility, vast research is needed to be done in medically pluralistic society like Bangladesh. In this regard, the Bhogobanian’s individuality concerning indigenous medicinal plant knowledge for curing disease can act as a great instance.